1984
DOI: 10.1071/bt9840387
|View full text |Cite
|
Sign up to set email alerts
|

Canopy Dynamics of Eucalyptus Maculata Hook. I. Distribution and Dynamics of Leaf Populations

Abstract: The canopy dynamics of a regenerated 16-year-old stand of pole and sapling E. maculata were studied for 2½ years by repetitive non-destructive measurements in tree crowns accessed from a 20 m high scaffold tower. Average canopy leaf area density over a sample plot of 36 m2 was 0.23 m2 m-3 at a leaf area index of 4.3. Some 75% of leaf area was held in the canopies of overstorey eucalypts above 10 m in height. Average size of leaves increased gradually from top to bottom of tree canopies. Foliage production was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
2
3

Year Published

1988
1988
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 0 publications
5
43
2
3
Order By: Relevance
“…(Attiwill 1966;Pook 1984). However, it has been reported that in lodgepole pine (Pinus contorta, Dean and Long 1986) and in oaks (Quercus alba and Q. velutina, Rogers and Hinckley 1979) the relationship between sapwood area and leaf mass is better described as curvilinear, meaning that large trees have a lower Huber value than small diameter trees of the same species.…”
Section: Growth Adjustments To Declining Carbon Balancementioning
confidence: 91%
“…(Attiwill 1966;Pook 1984). However, it has been reported that in lodgepole pine (Pinus contorta, Dean and Long 1986) and in oaks (Quercus alba and Q. velutina, Rogers and Hinckley 1979) the relationship between sapwood area and leaf mass is better described as curvilinear, meaning that large trees have a lower Huber value than small diameter trees of the same species.…”
Section: Growth Adjustments To Declining Carbon Balancementioning
confidence: 91%
“…In species with foliage longevities extending over several growing seasons, senescence of older foliage can occur throughout the year, although it is often more frequent during new foliage growth and development (Bargali and Singh, 1997;Gholz et al, 1991;Pook, 1984). However, older non-senescent foliage becomes gradually shaded due to new foliage formation and expansion (Brooks et al, 1994;Niinemets et al, 2006).…”
Section: Variations Driven By Environmental Modifications Foliage Dementioning
confidence: 99%
“…Today, foliage shoot growth of the overstorey trees in subtropical eucalypt open-forests and rainforests occurs during springtime-the driest time of the year in southeastern Queensland-and again in autumn at a reduced rate of production [101][102][103][104][105][106][107][108]. Flower production follows the shoot growth phenology in subtropical eucalypt open-forests [83].…”
Section: Seasonal Phenologymentioning
confidence: 99%